Profiling and Distribution of Metabolites of Procyanidin B2 in Mice by UPLC-DAD-ESI-IT-TOF-MSn Technique - Xiao, Ying; Hu, Zhongzhi; Yin, Zhiting; Zhou, Yiming; Liu, Taiyi; Zhou, Xiaoli; Chang, Dawei (Frontiers in Pharmacology, 2017)
The metabolite profiles and distributions of procyanidin B2 were qualitatively described using UPLC-DAD-ESI-IT-TOF-MSn without help of reference standards, and a possible metabolic pathway was proposed in the present study. Summarily, 53 metabolites (24 new metabolites) were detected as metabolites of procyanidin B2, and 45 of them were tentatively identified. 27metabolites were assigned as similar metabolites of (-)-epicatechin by scission of the flavanol interflavanic bond C4–C8, including 16 aromatic metabolites, 5 conjugated metabolites, 3 ring-cleavage metabolites, and 2 phenylvalerolactone metabolites. Additionally, 14 metabolites were conjugates of free procyanidin B2, comprising 9 methylation metabolites, 8 sulfation metabolites, 5 hydration metabolites, 2 hydroxylation metabolites, 1 hydrogenation metabolites, and 1 glucuronidation metabolites. The results of metabolite distributions in organs indicated that the conjugated reaction of free procyanidin B2 mainly occurred in liver and diversified metabolites forms were observed in small intestine. The metabolic components of procyanidin B2 identified in mice provided useful information for further study of the bioactivity and mechanism of its action.